2007
DOI: 10.3917/nrp.004.0089
|View full text |Cite
|
Sign up to set email alerts
|

La contraception masculine médicalisée : enjeux psychosociaux et craintes imaginaires

Abstract: Résumé La contraception masculine médicalisée, incarnée souvent par la « pilule pour l’homme », reste depuis plus de quarante ans à l’état d’une promesse médicale. Elle suscite peu de débats dans l’espace public et elle est caractérisée par une forte méconnaissance collective, voire une méfiance. Il s’agit en quelque sorte d’un objet « virtuel » qui, néanmoins, véhicule un imaginaire riche de projections autour de son modus operandi, son action, son efficacité et des changements possibles provoqués sur le plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The lack of knowledge in France regarding forms of male contraception and their mode of administration has already been identified [ 6 , 38 ] as a major obstacle to implementation and acceptability, and this study highlights the importance of information regarding this subject in both general and medical literature.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The lack of knowledge in France regarding forms of male contraception and their mode of administration has already been identified [ 6 , 38 ] as a major obstacle to implementation and acceptability, and this study highlights the importance of information regarding this subject in both general and medical literature.…”
Section: Discussionmentioning
confidence: 89%
“…Our results emphasize the importance of a non-hormonal contraceptive method for new fathers and future providers. A study on the psychosocial factors related to male medical contraception [ 38 ] showed that the lack of biological and medical knowledge regarding male contraception led to transposition of male to female contraception, such as the idea of a male hormonal pill [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The massive medicalisation of contraception places health professionals at the forefront in the acceptability [17] and dissemination [18] of a contraceptive method. Nevertheless, there are very few published data on practitioners' knowledge and practices regarding MC.…”
Section: Introductionmentioning
confidence: 99%
“…Since the role of MHC will be to decrease or stop the rate of fertility, this again may be perceived by men as threatening the status of traditional, hegemonic masculinity. Concerns around fertility and virility were highlighted in a study by Kalampalikis and Buschini [38], in which 46 semi-structured interviews were carried out with males and females in various sorts of relationships to understand how they constructed the male pill. They concluded that individuals used the female pill to inform their expectations of the advantages and disadvantages of the as yet imaginary male pill.…”
Section: Fear Of Losing Connotations Of Masculinitymentioning
confidence: 99%